Success stories from north-eastern India: Empowering rural livelihoods through scientific pig rearing and mushroom cultivation - Nath, Dipak; Singh, Uttam; Singha, A. K.; Mohanty, A. K.; Kadhri, Tabasum (Indian Farming, 2025)
The Farmer FIRST Programme (FFP), implemented in Central Agricultural University, Imphal, and ICAR Research Complex for NEH Region, Umiam, has significantly contributed to empowering rural livelihoods in north-eastern India through scientific interventions in pig rearing and mushroom cultivation. Through hands-on training, technical guidance, and input support, smallholder farmers and rural youth have adopted improved practices, transforming traditional piggery and mushroom production into profitable and sustainable enterprises. Integration of piggery, mushroom cultivation, fish farming, and vermicomposting demonstrates resource-efficient and diversified farming systems. These participatory, science-led, and locally adaptive interventions enhance income, food security, and employment, while fostering community-based knowledge sharing. The experiences underline the transformative potential of such initiatives to empower rural communities, build resilience, and promote sustainable livelihoods in smallholder farming landscapes of north-eastern India.